Efficient Aerobic Oxidative Coupling of Methyl Heteroarenes with Indoles - Zhang, Lei‐Yang; Wang, Nai‐Xing; Yan, Zhan; Wu, Yue‐Hua; Gao, Xue‐Wang; Feng, Ke; Lucan, Dumitra; Xing, Yalan (Chemistry : a European journal, 2023)
Direct oxidative coupling of inert C(sp3)−H bond has been a great challenge. Herein, an environmentally friendly aerobic oxidative coupling of α‐methyl substituted N‐heteroarenes with indoles is reported. A variety of diheteroaryl ketones were prepared in good yields (up to 72 %). This protocol features simple operation and broad substrates scope (26 examples). Significantly, a plausible mechanism about catalytic cycle was proposed, and two key intermediates were confirmed by high resolution mass spectrometry. A sustainable and environmentally friendly aerobic oxidative coupling of α‐methyl substituted N‐heteroarenes with indoles was first reported. A series of di‐heteroaryl ketones (26 examples) were obtained in moderate yields (up to 72 % yield), providing a highly atom‐economic approach for synthesizing complex pharmaceutical intermediates from small molecules. A plausible mechanism about cyclic catalysis was proposed and confirmed.